Chopin and the piano. A few remarks on a person’s relationship with an object - Bruliński, Michał (Chopin Review, 2025)
Fryderyk Chopin opened a new chapter in the social biography of the piano. The aim of my research was to explore Chopin’s unique relationship with his instrument from a ‘symmetrical’ perspective (the ‘turn to things’), distinguishing several categories in order to grasp the current topography of this field of study. The first category is the ‘archaeological’, oriented towards the market and the museum. The second is akin to the ‘reconstruction’ (making copies and renovating) of period instruments. In the ‘evaluative’ category, I have included Chopin’s observations concerning the craft of particular piano manufacturers. Another category can be described as ‘sociological’: Chopin’s correspondence gives us insight into the arcana of the field of music and the habitus of individual actors within the social process of playing for limited stakes (Bourdieu). It is worth emphasising that Chopin utilised the piano as a tool of class distinction. Another category, adjacent to the previous one, is that of ‘fetish’. The notion of fetish naturally pertains to the virtuoso’s relationship with the instrument. This category is related to the key dimensions of Chopin’s ‘domesticated’ space: his ‘den’ and ‘apartment’. The piano was his ‘closest friend’, to whom Chopin constantly ‘expressed himself ’, but against whom he also ‘inveighed’. He shared his sorrows and joys, released his anger and sought peace in the company of the piano. The symmetry of this relationship was revealed in dialogue: his piano ‘spoke’ and ‘sang’. Moreover, the piano was an important element of Chopin’s espaces imaginaires. One should not ignore prosaic but topical areas of the relationship: the instrument was also treated by Chopin as a piece of furniture, a tool for entertainment and an artifact in his interac- tions with women. The ‘patriotic issue’, connected with a mediated body of sources, is also noteworthy in the context of the reception of the phenomenon of the piano in Polish culture through the prism of Chopin. His intimate relationship with the piano was observed by relatives and students, spreading new piano affordances on a large scale.